The Effects of Outdoor Air Pollution on the Respiratory Health of Canadian Children: A Systematic Review of Epidemiological Studies - Laura A Rodriguez-Villamizar; Adam Magico; Alvaro Osornio-Vargas; Brian H Rowe (Canadian Respiratory Journal)
BACKGROUND: Outdoor air pollution is a global problem with serious effects on human health, and children are considered to be highly susceptible to the effects of air pollution.